Application of the Gallery Walk Method to Increase Activities and Learning Achievement of Law Students in Pancasila Education Courses - Fajriawati, Fajriawati; Harisman, Harisman (International Journal Reglement & Society (IJRS), 2020)
The purpose of this study was to increase student activity and learning achievement seen from the activities in mastering the material and carrying out the assignments given to achieve the expected learning achievement. That learning is no longer understood as merely a knowledge transfer process but must be practiced by students. As a form of implementation of activities carried out by each law student. The specific target of this research is as an effort to increase student activity and learning achievement, activities carried out by students are doing classroom practice through the gallery walk method. This research is in the form of Classroom Action ResearchÂ which consists of three cycles. The approach used in research is qualitative-quantitative to obtain research data. Quantitative data is obtained through giving tests, while qualitative data is based on the results of observations of the activities and achievements of students and lecturers in learning activities. Each cycle includes four stages, namely planning, action, observation, and reflection. The data sources of this research are all personnel who are directly involved in the research, namely first semester law students and lecturers. The tools used in data collection in this study were tests, observations and questionnaires. The types of data to be analyzed are quantitative and qualitative data. Quantitative data were obtained from the results of activity tests and student achievement on Pancasila learning material. Meanwhile, qualitative data in the form of observations of the gallery walk method of students in learning and lecturer activity data on the implementation of the action. Furthermore, the data will be analyzed qualitatively with the model of Miles and Huberman (2007) which includes (a) data reduction, (b) data presentation, and (c) drawing conclusions / verification and quantitative analysis by calculating achievement and activity observation data. learn law students using the Percentage Correction formula